PRODUCTION PROSTHETIC NOSE FOR CAD / CAM TECHNOLOGY: ADVANTAGES AND DISADVANTAGES - L.B. Yerys (Український стоматологічний альманах, 2018)
Traumatic defects individuals tend to remove surgically. If there are contraindications to surgery, facial defects, similar prostheses. CAD / CAM technologies are increasingly used in prosthetic dentistry, including the manufacture of artificial limbs ear, nose, orbit, upper and lower jaw. The purpose and goal of our work was to study computer technology and compared them to the production of classic maxillofacial prostheses and benefits of CAD / CAM technology in traditional prosthetic nose, for example. As an example, comparison of classical and modern production methods. Our result ektoprotezu nose and proposed methods are I.M.Oksman, S.Kosulyn. The main stages of manufacturing prosthetic nose for I.M.Oksman1. Remove the print of the face. 2. Create a prosthetic nose wax reproductions. 3. Location of functional edges. 4. Selection of color in the presence of the implant patient. 5. Gypsum wax reproductions prosthetic nose in a container.6. Replacement of wax on the plastic. 7. Connection prosthetic nose with frame glasses using pins and plastic cold polymerization. The main stages of manufacturing prosthetic nose S. Kosulin1. CT scan of the patient's face. 2. Optical scanning or pulled from the database fragments of the human person - "donor". 3. Combining electronic models plots person "donor" and the patient with the development model of the prosthesis.4. Development of the press molds for casting oil paper (wax model) prosthesis. 5. Development of programs for CNC machines for production of press - forms. 6. Production of press - forms on CNC machines. 7. Fill in the press - forms wax casting. 8. Fitting oil paper over printed in 3D - printer models face. 9. Production of rubber for oil paper form. 10. Draining silicone rubber prosthesis in shape.